2012
DOI: 10.1007/s10103-012-1088-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of low-level laser therapy on tracheal hyperresponsiveness and lung inflammation in rat subjected to intestinal ischemia and reperfusion

Abstract: Intestinal ischemia and reperfusion (i-I/R) is an insult associated with acute respiratory distress syndrome (ARDS). It is not known if pro- and anti-inflammatory mediators in ARDS induced by i-I/R can be controlled by low-level laser therapy (LLLT). This study was designed to evaluate the effect of LLLT on tracheal cholinergic reactivity dysfunction and the release of inflammatory mediators from the lung after i-I/R. Anesthetized rats were subjected to superior mesenteric artery occlusion (45 min) and killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Other experimental and clinical investigations also reported the positive effects of PBM on acute and chronic pulmonary inflammation, and acute pulmonary inflammation induced by intestinal ischemic-reperfusion [22][23][24]. Also, it has been observed that PBM may be useful for decreasing pulmonary fibrosis [25].…”
Section: Effect Of Pbm On Lung Inflammationmentioning
confidence: 90%
“…Other experimental and clinical investigations also reported the positive effects of PBM on acute and chronic pulmonary inflammation, and acute pulmonary inflammation induced by intestinal ischemic-reperfusion [22][23][24]. Also, it has been observed that PBM may be useful for decreasing pulmonary fibrosis [25].…”
Section: Effect Of Pbm On Lung Inflammationmentioning
confidence: 90%
“…They also studied a different model of ALI caused by intestinal ischemia and reperfusion (I/R), that produces an analogue of acute respiratory distress syndrome (ARDS) [78]. Rats were subjected to superior mesenteric artery occlusion (45 min) and received PBM (660 nm, 7.5 J/cm 2 ) carried out by irradiating the rats on the skin over the right upper bronchus for 15 and 30 min, and rats were euthanized 30 min, 2, or 4 h later.…”
Section: Effects Of Pbm On Inflammation In Animal Models Of Diseasementioning
confidence: 99%
“…LLLT can also accelerate cellular metabolic processes and increase synthesis of ATP [8] with an anti-inflammatory effect (release of inflammatory mediators, stimulation of microcirculation, absorption of exudates, and interference in the synthesis of prostaglandins) [12,13]. Research corroborates the influence of LLLT in relation to the recruitment of muscle fibers and the torque peak, in addition to delaying development of muscle fatigue, which contributes to a greater musculoskeletal performance [6,[14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 69%